Dynamic Interconnectedness and Risk Transmission in Green, Clean Energy, and Sustainable Markets - Jain, Suhasini; Puri, Neha; Rabbani, Mustafa Raza (Indian Journal of Finance, 2025)
Purpose : This study investigated the spillover effect and dynamic interconnectedness among green, clean, and sustainable markets. It identified the markets that are key transmitters and receivers, and it offered insights for investors and policymakers to optimize portfolio strategies and regulatory measures. Design/Methodology/Approach : The study employed the DY and BK models to analyze time frequency spillovers. Using the daily data, spillover was assessed across three time horizons that is short term (1–4 days), medium term (4–10 days), and long term (more than 10 days) to understand risk transmission. Findings : The results revealed that clean energy markets were the strongest transmitters of shocks, particularly in the medium and long terms; whereas, sustainable markets came out to be the largest receiver of shocks, with the highest vulnerability in the long term. Green Bonds (GB) and Carbon markets exhibited moderate spillover. Short-term spillover offered diversification opportunities; however, long-term spillovers were significant for risk mitigation. Practical Implication : Investors are recommended to balance their exposure between high-transmitting (clean energy) and high-receiving (sustainable market). This helps to optimize the risk-adjusted returns. GB are suitable for hedging as short-term spillovers offer better diversification opportunities. Originality/Value : The study contributed to existing financial research by analyzing volatility spillover among green, clean energy, and sustainable markets. Markets choose and use advanced econometric tools to provide a time–frequency-based risk assessment to investors and policymakers.